Reactive Oxygen Species: Its Effects on various Diseases - Marwal, Avinash; Verma, Sandeep S; Trivedi, Swati; Prajapat, Rajneesh (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2014)
A free radical is any molecule capable of independent existence that contains one or more free electrons. These free radicals fall under the broader category of reactive oxygen species (ROS). ROS such as O2- , H2O2, NO-, OH-, HOCl, ONOO- are toxic to cells. ROS act largely by driving several important molecular pathways that play important roles in pathologic processes including neurodegeneration. injury, atherosclerosis, and inflammatory responses and ischemia-reperfusion. ROS, as in various radicals ions leads to mitochondrial dysfunction and consequently other cell organelles damage either through environmental effect or through genetic or metabolic disorders. Reactive molecular species also disturbs other metabolic pathways in a manner that cells normal functionality gets disrupted. Though diseases caused by reactive oxygen species are many, this review has covered its effect on major diseases. The present review paper will provide the detail of mechanism of ROS and its effect on different pathological states.